2000
DOI: 10.1074/jbc.275.5.3403
|View full text |Cite
|
Sign up to set email alerts
|

Trp1, a Candidate Protein for the Store-operated Ca2+Influx Mechanism in Salivary Gland Cells

Abstract: The trp gene family has been proposed to encode the store-operated Ca 2؉ influx (SOC) channel(s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
239
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 265 publications
(264 citation statements)
references
References 38 publications
23
239
1
1
Order By: Relevance
“…Quantification of the TRPC1 band indicated an ϳ1.4-fold increase in DD patient samples ( Figure 1F), which was consistent with the confocal data described above. Although, the TRPC1 antibody used here is very specific (ϳ95% immunoreactivity toward TRPC1; Liu et al, 2000;Singh et al, 2001), similar results were also obtained using another B. Pani et al …”
supporting
confidence: 74%
See 2 more Smart Citations
“…Quantification of the TRPC1 band indicated an ϳ1.4-fold increase in DD patient samples ( Figure 1F), which was consistent with the confocal data described above. Although, the TRPC1 antibody used here is very specific (ϳ95% immunoreactivity toward TRPC1; Liu et al, 2000;Singh et al, 2001), similar results were also obtained using another B. Pani et al …”
supporting
confidence: 74%
“…However, the mechanism of this Ca 2ϩ -dependent regulation is not elaborately investigated. Our previous studies demonstrated that transient receptor potential canonical (TRPC)1 functions as store-operated calcium entry (SOCE) channel (Liu et al, 2000;Singh et al, 2001). Furthermore, a role of TRPC1 in the proliferation of neuronal and epithelial cells has been shown (Bollimuntha et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Number of reports has shown a reduced SOCE activity when TRPC expression was knocked down or knocked out [8][9][10][11]. When exogenously expressed some TRPC channels displayed SOCE activity [12][13][14]. However, numerous studies also demonstrated that TRPC channels did not operate as SOCE channels, but rather are gated by second messengers like Ca 2+ or diacylglycerol (DAG; [15][16][17]).…”
Section: Introductionmentioning
confidence: 99%
“…Highly discrepant results obtained in heterologous expression studies and the inability to reproducibly reconstitute native capacitative Ca 2+ entry channels by overexpression of a TRPC species led to the hypothesis that TRPC proteins are pore-forming subunits, which may require association with unidentified endogenous proteins to form a SOCE (or CCE) channel (Sinkins et al 1998;McKay et al 2000). This concept was later on continuously supported by studies using antisense and siRNA knock-down strategies or expression of dominant negative TRP species to suppress or modify endogenous SOCE (Groschner et al 1998;Liu et al 2000;Philipp et al 2000;Wu et al 2000;Baldi et al 2003;Liu et al 2003;Wu et al 2004) and appears reasonable and sufficient to explain the phenomenon that expression of a TRPC species generates divergently regulated Ca 2+ entry pathways in different cell systems or even in one host cell type at different levels of expression . The concept implies that a given TRPC species is able to associate with other channel and auxiliary subunits to form distinct signaling complexes with a composition dependent on the availability of the complex partners.…”
Section: Introductionmentioning
confidence: 99%